Use of Tri-Ponderal Mass Index in Predicting Late Adolescent Overweight and Obesity in Children Aged 7–18 - Wang, Xijie; Ma, Jun; Huang, Sizhe; Dong, Bin; Dong, Yanhui; Yang, Zhaogeng; Hu, Jie; Liang, Wannian (Frontiers in Nutrition, 2022)
Background Current reference systems using body mass index (BMI) or BMI-z-scores to estimate overweight and obesity risk in adolescents are complex to use. An easy and effective measure and cutoffs are in need for parents and grassroots health workers such as the tri-ponderal mass index (TMI). Objective To test whether cohort-derived TMI could be efficient for obesity prediction, and to find out whether simplified TMI cutoffs could be used in the prediction. Methods Data was obtained from a 12-year retrospective growth cohort generated in Guangdong, China. 17,815 children (53.9% were boys) with 151,879 annually-conducted follow-ups between 2005 to 2016 were involved. Late adolescent overweight and obesity were defined based on the BMI-z-score (WHO 2007 growth reference) of the last measurement, which happened at the mean age of 17.2 (SD: 0.7) for both sexes. Analysis of the area under ROC curve (AUC) was used to find the most appropriate cutoff. Results In total, 9604 boys and 8211 girls were included in the final analysis. TMI cutoffs performed better than WHO BMI cutoffs in the prediction of late adolescent overweight and obesity, with all corresponding AUCs greater than 0.7. The simplified TMI cutoffs used to predict late adolescent overweight and obesity were 13.1 kg/m3 and 14.1 kg/m3 for children aged 7 to 15, respectively, with corresponding AUCs ranged from 0.7315 (standard error, SE: 0.0132) to 0.9367 (SE: 0.0052). The cutoffs for predicting late adolescent overweight and obesity for children aged 16 to 18 were 14.0 kg/m3 and 15.8 kg/m3, respectively, with the corresponding AUC ranged from 0.9189 (SE: 0.0048 ) to 0.9841 (95% CI: 0.0027). Conclusions TMI with the ease of administration in practice could be a promising alternative screening tool to BMI for the prediction of late adolescent overweight and obesity.